Analisis Pengaruh Risiko Pembiayaan, Risiko Likuiditas, dan Risiko Pasar Terhadap Profitabilitas dengan Nilai Tukar Sebagai Variabel Moderasi (Studi pada Perbankan yang Terdaftar di Bursa Efek Indonesia) - Astuti, Tifany Yeldi; Putri, Anne (LPPM Institut Pendidikan Nusantara Global, 2025)
Using the exchange rate as a moderator, this study aims to analyze the relationship between profitability, credit risk (as assessed by nonperforming loans), liquidity risk (as measured by loan default rates), and market risk (as measured by net interest margin) in banks listed on the Indonesia Stock Exchange. Banks that will be trading on the Indonesia Stock Exchange in 2020 and 2022 are the subject of this study. For our investigation, we employ a purposive sample strategy. Panel data regression, which integrates cross-sectional and time series data, is applied to the data in Eviews 10 software. The results of the test, which use the Random Effect Model method, demonstrate that the NPL, LDR, and NIM variables all have an impact on Return On Assets at the same time, as evidenced by a Prob value (F-Statistic) of 0.0000 <0.05. Positive effects on ROA are produced by the NIM variable. Nevertheless, the LDR and NIM variables have a negative impact on ROA. The study found that NPL, LDR, and NIM add up to 22.68% of ROA. In the fiscal years 2020–2022, there was no indication from the interaction test that the exchange rate modifies the effect of non-investment margins, non-performing loans, and non-investment credit on return on assets (ROA) for Indonesia Stock Exchange-listed banks